Ability To Use Digitalization In Increasing The Competitive Advantages Of Msmes In Indonesia: Systematic Literature Review (SLR) - Amelia Setyawati; Amelia Suggangga; Nyuherno Aris Wibowo; Adelia Rahma; Farij Ibadil Maula (International Journal of Economics and Management Research, 2023)
The business world is currently experiencing disruption, the impact of technological and digital developments. the emergence of various kinds of sophisticated technological advances such as the Internet of Things (IoT), Advanced Robotics, 3D Printing, Artificial Intelligence and other technologies that enable changes from conventional work systems to automation and digital integration. With the phenomenon of technological disruption, a problem is being faced by MSMEs, the competitive advantage possessed by MSME players in Indonesia is decreasing. Recognizing that there is a gap in the use of technology in productive and not consumptive use, it is necessary to carry out further research, to find out more deeply, whether the use of technology in MSMEs will really have an impact on building and maintaining an MSMEs. The method used in this research is Systematic Literature Review (SLR) by collecting and analyzing journals related to keywords. Based on the literature study conducted, it was found that the competitive advantage of MSMEs in Indonesia, one of which is that MSMEs have the organizational ability to attract customers and build prestige for the organization or its products and increase the value felt by customers and achieve their satisfaction which is also the ability to provide various values to customer. Competitive advantage is not fixed, but needs to continuously evolve to keep in touch with various developments, economic, political, social and technological. The results of this research have implications for two things: first, the behavior of MSMEs is expected to continue to upgrade capabilities creatively, innovatively and adaptively, secondly, the government is expected to continue to improve and complement MSMEs facilities evenly and improve mentoring / training programs for MSMEs.